2007
DOI: 10.1177/039139880703000405
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Hepatitis B with Lamivudine in Renal Transplant Recipients

Abstract: Treatment of chronic hepatitis B in renal transplant recipients remains one of the major problems in clinical nephrology. Lamivudine is considered to be a drug of choice for these patients, however, its efficacy in patients with hepatitis B after renal transplantation (RT) has not been completely proven. Twenty-two RT recipients treated with lamivudine were evaluated. The duration of treatment was 15.6±1.9 months. Fourteen patients (64%) had normalization of aminotransferase (ALT); in 9 of them (41% of the who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Because of the scarcity of histologic data, the difference in outcome comparing less advanced disease posttransplantation to patients with advanced fibrosis was not elucidated. Although few studies have post-RT liver biopsy data, a recent report from Zubkin et al demonstrated a decrease in liver inflammatory activity and fibrosis in 3 of 4 HBV-infected recipients post-RT treated with lamivudine [53]. In other reports, lamivudine monotherapy was given for 24 to 69 months (n=116 patients) [54][55][56][57][58].…”
Section: Therapy Of Hepatitis B After Rt: Lamivudinementioning
confidence: 99%
“…Because of the scarcity of histologic data, the difference in outcome comparing less advanced disease posttransplantation to patients with advanced fibrosis was not elucidated. Although few studies have post-RT liver biopsy data, a recent report from Zubkin et al demonstrated a decrease in liver inflammatory activity and fibrosis in 3 of 4 HBV-infected recipients post-RT treated with lamivudine [53]. In other reports, lamivudine monotherapy was given for 24 to 69 months (n=116 patients) [54][55][56][57][58].…”
Section: Therapy Of Hepatitis B After Rt: Lamivudinementioning
confidence: 99%
“…[10] Unlike interferon, lamivudine does not have an immunomodulatory effect and therefore can be safely used in renal transplant patients. There are some studies in literature on the role of lamivudine in these patients;[1129] however, there is no report from India on efficacy and tolerability of lamivudine in renal transplant patients with HBV infection. The aim of the present study was to report the effectiveness and safety of lamivudine therapy in HBV-positive RT patients.…”
Section: Introductionmentioning
confidence: 99%